A Packet Loss Protection Scheme Joint Deterministic Network Coding and Random Linear Network Coding for H.264/AVC - Cuiping Jing; Xingjun Zhang; Yifei Sun; Huali Cui; Xiaoshe Dong (2011 fifth FTRA International Conference on Multimedia and Ubiquitous Engineering : 28-30 June 2011, 2011)
Video streaming applications over lossy packet networks is a challenging task due to a number of factors such as delay, fix bandwidth allocation, and packet loss. The conventional Forward Error Correcting (FEC) code and automatic repeat requestret (ARQ) methods will become ineffective to transmit video streaming for the reason that video frame errors appear in bursts which will lead to reconstruct the video frame very difficult over the lossy packet network. In this paper, we focus on an effective packet loss protection scheme joint deterministic network coding (DNC) and random linear network coding (RLNC) for H.264/AVC video transmission. Considering the complexity of RLNC algorithm, the transmission scheme should make some improvements. Firstly, the source node encodes data packets based on the deterministic network coding, which will improve the efficiency of coding. Secondly, RLNC process at the intermediate nodes needs to do some limited operations for the random encoding coefficient vectors to reduce the redundancy packets in the network. Thirdly, the decoding process at the destination nodes should be simplified. We demonstrate the effectiveness of this approach by system implementation and performance evaluation. Experimental results are given to demonstrate the significant improvement of H.264/AVC streaming reconstructive video quality over the lossy packet network, and the improvement is comparably more remarkable when the packets loss dramatically.